Caracterización molecular de frutos de chilacayote (Cucurbita ficifolia Bouché) mediante AFLP - Moya Hernández, Araceli (Universidad Autónoma Metropolitana, 2015)
Cucurbita ficifolia Bouché is a wild crop known in Mexico as "chilacayote" whose fruits are used as food. The fruits show a pericarp of different colors (whitish, creamy, various shades of green, striped or speckled) and seeds of white or black color. Recent studies report that this specie has remarkable hypoglycemic properties. However, there is not any report which shows if the hypoglycemic properties depend on the phenotypic characteristics of the species. The objectives of this study were: 1) Evaluate the phenotypic characteristics of C. ficifolia of different producing areas through a molecular differentiation. 2) Determine if the aqueous extracts of the fruits from different regions have the same hypoglycemic effect. In order to achieve the first objective, young and fresh leaves of chilacayote from the states of Hidalgo, Tlaxcala, Michoacán, Puebla and Mexico State were collected. DNA samples were extracted to analyze the genetic diversity through AFLP (Amplified Fragment Length Polymorphism). A binary matrix of presence-absence was built, the genetic distances were calculated and a dendrogram was obtained with the UPGMA method (Unweighted Pair Group Method with Arithmetic Mean). For the second objective, an aqueous extract from the fruit was obtained and 500 mg extract/kg was administered to male mice of 35 g (strain CD-1). Glibenclamide (20 mg/kg) was used as positive control and an isotonic saline (4 ml per kg) as negative control. The molecular results showed an 89.4-98.5% of similarity among samples indicating that all the fruits of chilacayote are genetically similar despite their morphological differences. These results suggest that there is a significant effect of climatic conditions of each region as the dendrogram grouped by geographical area. All fruits showed better the hypoglycemic effect of glibenclamide. However the fruits from Ixtapaluca, Edo. De Mexico showed a healthier effect than Hidalgo, Michoacán, Tlaxcala and Puebla.; Cucurbita ficifolia Bouché (C. ficifolia) es un cultivo silvestre conocido en México como "chilacayote" cuyos frutos se utilizan como alimento. Los frutos presentan un pericarpio de diferentes colores (blanco, cremoso, varios tonos de verde, rayado o moteado) y semillas de color blanco o negro. Estudios recientes reportan que esta especie tiene propiedades hipoglucemiantes notables. Sin embargo, no hay ningún informe que demuestre si las propiedades hipoglucemiantes dependen de las características fenotípicas de la especie. Los objetivos de este estudio fueron: 1) Evaluar las características fenotípicas de C. ficifolia de diferentes zonas de producción a través de una diferenciación molecular. 2) Determinar si los extractos acuosos de los frutos de diferentes regiones tienen el mismo efecto hipoglucémico. Para lograr el primer objetivo, se recolectaron hojas jóvenes y frescas de chilacayote de los estados de Hidalgo, Tlaxcala, Michoacán, Puebla y Estado de México. Se extrajo ADN de las muestras para analizar la diversidad genética mediante AFLP (por sus siglas en inglés Amplified Fragment Length Polymorphism). Se construyó una matriz binaria de presenciaausencia, se calcularon las distancias genéticas y se obtuvo un dendrograma con el método UPGMA (por sus siglas en inglés Unweighted Pair Group Method with Arithmetic Mean). Para el segundo objetivo, se obtuvo un extracto acuoso de la fruta y se administraron 500 mg de extracto/kg a ratones machos de 35 g (cepa CD-1). Se utilizó Glibenclamida (20 mg/kg) como control positivo y solución salina isotónica (4 ml/kg) como control negativo. Los resultados moleculares mostraron un 89.4-98.5% de similitud entre las muestras, lo cual indica que todos los frutos de chilacayote son genéticamente similares a pesar de sus diferencias morfológicas. Estos resultados sugieren que existe un importante efecto de las condiciones climáticas de cada región ya que el dendrograma agrupo a los frutos analizados por área geográfica. Todas las frutas mostraron un mayor efecto hipoglucémico que el de la glibenclamida siendo los frutos provenientes de Ixtapaluca, Edo. de México los que exhibieron un mejor efecto que los de Hidalgo, Michoacán, Tlaxcala y Puebla.